Aplikasi Metode Adams Bashforth Moulton Dalam Memprediksi Pertumbuhan Penduduk Di Kota Ambon - Fikram Radjab; Francis Yunito Rumlawang (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2025)
The increasing population in Ambon City can cause various problems both social and environmental problems such as lack of residential land, clean water needs, transportation problems to health. This study is to examine the increasing population of Ambon City, this study will also predict the population in Ambon City in the following year using historical data using the fourth-order Adams Bashforth Moulton method approach from Verhulst modeling. This research produces accurate forecasting with a very small relative error value, with an area of 377km2 and a predicted population of 372,725 in 2030. The Adams Bashforth Moulton method as a Verhulst model is very effective for decision making in predicting population growth in Ambon City.